Laparoscopy-assisted D2 radical distal gastrectomy for gastric cancer (Billroth II anastomosis) - Yao, Hanhui; Huang, Qiang; Zhu, Zhiqiang; Liang, Wei (Chinese Journal of Cancer Research; Vol 25, No 4 (August 24, 2013): Chinese Journal of Cancer Research, 2013)
Laparoscopic radical gastrectomy has been increasingly applied in China. However, how to reduce surgery-related trauma, shorten operative time and achieve the long-term prognosis equal to the conventional open surgery is still hot research topics. Along with the change in learning curve and the optimization of endoscopic techniques, laparoscopic lymph node dissection can achieve or even exceed the extent that can be achieved in open surgery. Therefore, it has gradually replaced the conventional digestive tract reconstruction using an auxiliary incision. By completing the laparoscopic digestive tract reconstruction with EndoGIA, we describe the laparoscopy-assisted D2 radical distal gastrectomy for gastric cancer (Billroth II anastomosis).